Immunosuppressive drugs and diet interact to modify the gut microbiota and cardiovascular risk factors, and to trigger diabetes - Paul Gabarre; Roberto Palacios; Kevin Perez; Philippe Seksik; Benjamin Bonnard; Christopher Loens; Clara Lefranc; Jean-Paul Pais de Barros; Louis Anjou; Yanis Tamzali; Noël Zahr; Frédéric Jaisser; et al. (PLoS ONE, 2025)
Background Kidney transplant recipients are prescribed an immunosuppressive therapy (IST) and some of them follow a high fat diet (HFD) despite medical recommendations. Both are frequently associated with gut microbiota changes and metabolic disorders. We aimed at precisely identifying the effect of the IST and the HFD on metabolic parameters and the gut microbiota in mice, and at establishing correlations between the latters. Methods 8-week-old male mice were treated with IST (a combination of prednisone, mycophenolate mofetil and tacrolimus) or not and were fed HFD or standard chow. Metabolic parameters were measured, and the gut microbiota was explored by the quantification of specific bacterial groups by qPCR and by 16S rDNA sequencing. Results The HFD increased insulinemia and decreased the fecal proportion of Bacteroidetes and of Bacteroides. The IST increased systolic blood pressure and the fecal proportion of Escherichia coli. The HFD and the IST administered together resulted in an additive effect on glucose intolerance, high fasting blood glucose, homeostasis model assessment of insulin resistance (HOMA-IR), percentage of fat mass, blood triglyceride, blood cholesterol, and endotoxemia. On the opposite, the HFD and the IST had antagonistic effects on body weight, the proportion of Firmicutes, the Firmicutes/Bacteroidetes ratio, and the proportion of Clostridium leptum, Bifidobacterium, and Lactobacillus in the feces. Finally, we found that the correlations between gut bacterial communities and metabolic consequences of the HFD were altered by the IST. Conclusion The IST and the HFD have specific consequences on the gut microbiota and metabolism. We hypothesize that the metabolic consequences are at least partially mediated by IST/HFD-induced dysbiosis.